Powered by storytelling : excavate, craft, and present stories to transform business communication - Nossel, Murray (McGraw-Hill, 2018)
Everyone needs to communicate well to succeed in business. And everyone has a story to tell. This groundbreaking guide shows you how to tell your story, connect with your audience, and achieve results. --